Unilateral liquidation of state contracts ruled by private law: problems of the concept of exorbitant power in the jurisprudence of the Colombian Council of State (Euro-Latin American Journal of Administrative Law, 2025)
This article discusses the jurisprudential thesis of the Colombian Council of State according to which state entities governed by private law, in their contractual activity, can unilaterally liquidate their contracts if they have stipulated it. The high court argues that this power does not imply an exorbitant power and that, therefore, for its exercise an administrative act is not issued but a contractual act. The paper explains the theoretical and dogmatic problems of this approach. It is concluded that unilateral liquidation is an exorbitant power that materializes in an administrative act, because the identification of that type of prerogatives must be consistent with its conceptual characterization in academic methodology and with the criterion of systematic interpretation in the legal system.
Keywords: exorbitant power; unilateral settlement; administrative act; administrative law; private law.